ChemInform Abstract: Thioboration of α, β‐Unsaturated Ketones and Aldehydes Toward the Synthesis of β‐Sulfido Carbonyl Compounds. Issue 27 (18th June 2015) - Civit, Marc G.; Sanz, Xavier; Vogels, Christopher M.; Webb, Jonathan D.; Geier, Stephen J.; Decken, Andreas; Bo, Carles; Westcott, Stephen A.; Fernandez, Elena
Abstract The synthesis of β‐thio substituted carbonyl compounds is achieved by uncatalyzed reaction of α, β‐unsaturated carbonyl compounds with thiodioxaborolanes under mild reaction conditions.